Wave propagation through alumina-porous alumina laminates. Issue 1 (January 2015) - Sellappan, Pathikumar; Wang, Erheng; Santos, Christian J. Espinoza; On, Tommy; Lambros, John; Kriven, Waltraud M.
Abstract A Brazilian disk geometry of an alumina layered composite with alternating dense and porous layers was dynamically loaded using a Split-Hopkinson Pressure Bar (SHPB) apparatus under compression. High-speed imaging and transmitted force measurements were used to gain an insight into stress wave propagation and mitigation through such a layered system. Uniformly distributed porosities of 20 and 50 vol% were introduced into the interlayers by the addition of fine graphite particles which volatilized during heat treatment. Brazilian disk samples were cut from the cylinders which were drilled out of the sintered laminated sample. The disks were subjected to dynamic impact loading in perpendicular and parallel orientations to the layers in order to investigate the influence of the direction of impact. The dynamic failure process of the layered ceramic consisted of the initiation and propagation of the cracks mainly along the interphases of the layers. Upon impact, the impact energy was dissipated through fracture in parallel orientation (0°) but transmitted in perpendicular (90°) orientations. The high degree of correlation between the transmitted force, microstructure and orientation in which the layered systems were impacted is discussed.